Microalgae-based biogas slurry treatment integrated with sustainable aviation fuel production: from waste to high-value bio-jet fuel - Binbin Zhu; Hongyin Chen; Jing Lv; Wenjun Zhang; Jiaming Liu; Ruirui Liu; Bishu Qi; Shuhui Li; Chengyu Yang; Xiao Yan; Zijian Xia; Xingliang Xu; et al. (Bioresource Technology, 2026)

Polyphase of uranium mineralization in granite-related deposits: Insights from the geochronology and geochemistry of pitchblende and coffinite in the Xiwang uranium deposit, South China - Bin Liu; Weifeng Chen; Haidong Li; Jiaming Qi; Liang Qiu; Hongfei Ling (Applied Geochemistry, 2026)

Petrogenesis of Yanshanian granites in the Guidong complex, Northern Guangdong: Implications for uranium mineralization - Haiyang Wang; Changqian Ma; Jiayong Pan; Fujun Zhong; Fei Xia; Xiangping Gu; Guanghua Liu; Zhengle Chen; Jungang Liu; Jiaming Qi (Acta Geochimica, 2026)

Environmental exposure to bisphenol S suppresses white adipocyte beiging and energy expenditure via CYP2E1 in mice - Qi Liu; Yuancheng Shao; Jiaming Xue; Yicheng Jiang; Shuai Chen; Dongmei Wang; Yan Zhou; Jie Zhao; Wei Gao; Liming Tang (Environmental Pollution, 2026)

Rapid Visual Detection of Decapod Iridescent Virus 1 ( DIV1 ) by RPA Combined With LFS - Quanling Mu; Cunbao Ding; Ying Xie; Xi Zhen; Xianrui Wang; Tongaobo Qi; Jiaming Zhang; Yakun Yu (Journal of Fish Diseases, 2026)
Decapod iridescent virus 1 (DIV1) causes severe disease outbreaks in shrimp and crab culture areas. A simple, rapid, and visual DIV1 assay is important for the control of viral diseases. This study presented a novel DIV1 detection method that combines recombinase polymerase amplification (RPA) and lateral flow strip (LFS). After selecting primers and probes, we optimised the concentration of the reverse primers, reaction time, as well as reaction temperature of RPA‐LFS detection. RPA can amplify the target gene within 18 min at a constant temperature of 38°C, and LFS can observe the amplification results within 3 min. Importantly, there is no cross‐reactivity with other infectable shrimp viruses and pathogens, such as WSSV, IHHNV, TSV, EHP, CMNV, YHV, MrNV samples, as well as Vp AHPND . In addition, RPA‐LFS has high detection sensitivity, with a lower detection limit of 1.12 × 10 1 copies/μL. Using 110 field samples, the results of qPCR recommended by WOAH (OIE) and RPA‐LFS were identical, indicating that RPA‐LFS is as reliable as qPCR. The RPA‐LFS assay is a valuable tool for the rapid and accurate detection of DIV1.

Multifactorial synergistic strategies mediate the biocontrol of Fusarium oxysporum-induced root rot by Bacillus velezensis SYL-3 - He Liu; He Huang; Yuzhe Wang; Mengnan An; Jiaming Bai; Jianquan Zhou; Haiyang Lan; Aiwei Qi; Baoan Song; Yuanhua Wu (Pesticide Biochemistry and Physiology, 2026)

Integrated network toxicology, molecular docking and transcriptomics reveal the mechanistic role of phthalate esters in metabolic disease pathogenesis - Yuancheng Shao; Qi Liu; Yicheng Jiang; Gang Zhou; Xihan Gu; Shufan Zhang; Shuai Chen; Jiaming Xue; Liming Tang (Food and Chemical Toxicology, 2026)

Potential strategies of natural products in the treatment of atherosclerosis: Focusing on modulating macrophage polarization - Wenjie Zhao; Peng Sun; Jiaming Huan; Lei Zhang; Shijing Peng; Tong Jiang; Linghui Kong; Xinghao Zhu; Wenqing Yang; Dongmei Qi; Yunlun Li (PharmaNutrition, 2025)

MKAIS: A Hybrid Mamba–KAN Neural Network for Vessel Trajectory Prediction - Caiquan Xiong; Jiaming Li; Yuzhe Zhuang; Xinyun Wu; Mao Luo; Qi Wang (Journal of Marine Science and Engineering, 2025)
Vessel trajectory prediction (VTP) plays a critical role in maritime safety and intelligent navigation. Existing methods struggle to simultaneously capture long-term dependencies and nonlinear dynamic patterns in vessel movements. To address this challenge, we propose MKAIS, a novel trajectory prediction model that integrates the selective state space modeling capability of Mamba with the strong nonlinear representation power of Kolmogorov–Arnold Networks (KAN). Specifically, we design a feature-separated embedding strategy for AIS inputs (longitude, latitude, speed over ground, course over ground), followed by an MKAN module that jointly models global temporal dependencies and nonlinear dynamics. Experiments on the public ct_dma dataset demonstrate that MKAIS outperforms state-of-the-art baselines (LSTM, Transformer, TrAISformer, Mamba), achieving up to 16.65% improvement in the Haversine distance over 3 h prediction horizons. These results highlight the effectiveness and robustness of MKAIS for both short-term and long-term vessel trajectory prediction.

Enhancing vessel trajectory prediction with bi-state space and squeeze excitation attention - Caiquan Xiong; Jiaming Li; Xinyun Wu; Donghua Liu; Qi Wang; Rong Gao; Jinjia Ruan (Ocean Engineering, 2025)

Low-dose exposure to microplastics retards meiotic maturation via HDAC3 insufficiency - Qi Zhao; Ming Zong; Entong Song; Hongye Linghu; Xuanwen Li; Baicui Wang; Songling Xiao; Wanchun Guan; Jianzhong Su; Jiaming Zhang; Jingzhang Ji; Qingran Kong (Science China Life Sciences, 2025)

Cyclization: A potential effective modification strategy for umami peptides - Zhiyong Cui; Yanyang Yu; Tianxing Zhou; Chengliang Qi; Jiaming Gu; Ninglong Zhang; Xiaoxiao Feng; Zhiwei Zhang; Yiwen Zhu; Yin Zhang; Wenli Wang; Yuan Liu (Food Chemistry, 2025)

Fabrication and saltiness enhancement of salt hollow particles by interface migration - Kailin Ye; Jiafeng Chen; Xinyu Zhang; Jiaming Qi; Zihan Qin; Jinmei Wang (Food Research International, 2025)

Effect of heat treatment on the stability of ultrasound-assisted cross-linked myofibrillar protein-stabilized emulsion filler phases via rheology and tribology - Ye Tao; Jiaming Cai; Peng Wang; Jiahui Chen; Lei Zhou; Qi Wang; Zhen Li; Jingyu Wang; Xinglian Xu (Food Hydrocolloids, 2025)

Innovative approach to enhancing phosphogypsum mechanical properties and stabilizing/solidifying contaminants - Lina Xiao; Jiaming Zhang; Yi Luo; Xiaojian Qi; Javid Hussain; Guosheng Jiang (Sustainable Chemistry and Pharmacy, 2024)

Evaluation of a novel attapulgite loaded sulfidized nanoscale zero-valent iron for immobilization of Pb in sediment: Performance, microenvironmental response, and mechanisms - Siqi Wen; Weilong Lin; Qi He; Yiqun Xu; Xiaoyu Shi; Jiaming Guo; Yang Gao; Wenjing Xue (Chemical Engineering Journal, 2024)

Mechanism and toxicity assessment of Cu0/Fe3O4 activated persulfate based on the acceleration cycle of Fe3+/Fe2+ for the degradation of methyl orange - Lanhe Zhang; Qi Zhang; Chuan Xiao; Yanping Jia; Jiaming Wu (Journal of Water Process Engineering, 2024)

Amino-modified biochar-supported S-nZVI for Cr(VI) and total Cr removal from water: Parameter regulation, kinetic and mechanistic analysis - Yiqun Xu; Jiaming Guo; Siqi Wen; Xiaoyu Shi; Qi He; Weilong Lin; Yu Wang; Yang Gao; Rongzhong Wang; Wenjing Xue (Journal of Water Process Engineering, 2024)

Preparation of salicylic acid nano-protectant with dual synergistic mechanism: High direct fungicidal activity and plant defence toward cotton Verticillium wilt - Jiaming Yin; Jiajia Zhao; Zeng Wang; Fan Xue; Qi Wang; Huiming Guo; Hongmei Cheng; Jie Li; Jie Shen; Meizhen Yin; Xiaofeng Su; Shuo Yan (Chemical Engineering Journal, 2024)

Binary-Network structured PI@SiO2 nanofibrous composite aerogels with temperature invariant superelasticity for thermal insulation - Qicheng Xue; Nanxi Dong; Peiqi Fan; Daolei Lin; Guofeng Tian; Jun Liu; Jiaming Wei; Shengli Qi; Dezhen Wu (Chemical Engineering Journal, 2024)

High performance self-assembled sulfidized nanoscale zero-valent iron for the immobilization of cadmium in contaminated sediments: Optimization, microbial response, and mechanisms - Yiqun Xu; Hongdou Liu; Siqi Wen; Jiaming Guo; Xiaoyu Shi; Qi He; Weilong Lin; Yang Gao; Rongzhong Wang; Wenjing Xue (Journal of Hazardous Materials, 2024)

Affecting factors and mechanism of removing antibiotics and antibiotic resistance genes by nano zero-valent iron (nZVI) and modified nZVI: A critical review - Wenjing Xue; Xiaoyu Shi; Jiaming Guo; Siqi Wen; Weilong Lin; Qi He; Yang Gao; Rongzhong Wang; Yiqun Xu (Water Research, 2024)

Using geodetic measurements derived terrestrial water storage to investigate the characteristics of drought in Yunnan, China - Chao Chen; Rong Zou; Zhiwei Fang; Jiaming Cao; Qi Wang (GPS Solutions, 2024)
The use of the global navigation satellite system (GNSS) for monitoring changes in terrestrial water storage (TWS) is growing. However, the density of GNSS stations is sparse in most areas, and the widely used Green’s function (GF) method cannot provide a satisfactory resolution for inversion problems. As the Slepian basis function (SBF) method has been successfully used for gravity inversions, GNSS geodesists have recently applied the SBF method to GNSS displacements. However, the evaluation of TWS differences inferred from GNSS using the SBF and the GF has been rarely assessed. In this study, we use both the GF and the SBF methods to investigate the TWS in Yunnan by using more than ten years (2010–2021) of GNSS observations. We observe a remarkable consistency between the two inversion methods employed for GNSS data, as well as a strong agreement with equivalent water heights (EWH) inferred from the Gravity Recovery and Climate Experiment (GRACE) and GRACE Follow-On (GFO), hydrological model (GLDAS-NOAH), and precipitation data, despite variations in the amplitude. Furthermore, affected by monsoon climate and topography, Yunnan is prone to drought. We analyze the main nine drought events, evaluate the connection between GNSS-inverted TWS during 2010–2021, and find that almost all droughts in Yunnan occurred during the "trough period" within the GNSS-DSI.

Enhancement of sodium salty taste modulate by protease-hydrolyzed Gum Arabic - Kailin Ye; Jiaming Qi; Yang Zhang; Jinmei Wang; Jian Guo; Xiaoquan Yang (Food Hydrocolloids, 2023)

Spatiotemporal patterns of fire-driven forest mortality in China - Jie Zhao; Jiaming Wang; Yifan Meng; Ziqiang Du; Hui Ma; Linghua Qiu; Qi Tian; Liang Wang; Mengyang Xu; Hongfei Zhao; Chao Yue (Forest Ecology and Management, 2023)

Gene polymorphism of chalcone isomerase influence the accumulation of flavonoids in licorice (Glycyrrhiza spp.) - Xiaodong Zhang; Shaokai Tian; Lin Qi; Wendong Li; Jiaming Hou; Lin Yang; Zhixin Zhang; Ying Liu (Genetic Resources and Crop Evolution, 2021)

Gene Biomarkers Derived from Clinical Data of Hepatocellular Carcinoma - Jiaming Qi; Jiaxing Zhou; Xu-Qing Tang; Yaolai Wang (Interdisciplinary Sciences: Computational Life Sciences, 2020)

Evaporite karst and resultant geohazards in China - Lu Yaoru; Zhang Feng’e; Qi Jixiang; Xu Jiaming; Guo Xiuhong (Carbonates and Evaporites, 2002)